Referral-based Job Search Networks - Dustmann, Christian; Glitz, Albrecht; Schönberg, Uta; Brücker, Herbert (Review of Economic Studies, 2016)
This article derives novel testable implications of referral-based job search networks in which employees provide employers with information about potential new hires that they otherwise would not have. Using comprehensive matched employer–employee data covering the entire workforce in one large metropolitan labour market combined with unique survey data linked to administrative records, we provide evidence that workers earn higher wages and are less inclined to leave their firms if they have obtained their job through a referral. These effects are particularly strong at the beginning of the employment relationship and decline with tenure in the firm, suggesting that firms and workers learn about workers' productivity over time. Overall, our findings imply that job search networks help to reduce informational deficiencies in the labour market and lead to productivity gains for workers and firms.